Combination of anginex gene therapy and radiation decelerates the growth and pulmonary metastasis of human osteosarcoma xenografts - Kai Zhao; Shang‐You Yang; Jun Geng; Xuan Gong; Weiming Gong; Lin Shen; Bin Ning (Cancer Medicine)
Abstract Investigate whether rAAV‐anginex gene therapy combined with radiotherapy could decrease growth and pulmonary metastasis of osteosarcoma in mice and examine the mechanisms involved in this therapeutic strategy. During in vitro experiment, multiple treatment regimes (rAAV‐eGFP, radiotherapy, rAAV‐anginex, combination therapy) were applied to determine effects on proliferation of endothelial cells (ECs) and G‐292 osteosarcoma cells. During in vivo analysis, the same multiple treatment regimes were applied to osteosarcoma tumor‐bearing mice. Use microcomputed tomography to evaluate tumor size. Eight weeks after tumor cell inoculation, immunohistochemistry was used to assess the therapeutic efficacy according to microvessel density (MVD), proliferating cell nuclear antigen (PCNA), and terminal‐deoxynucleotidyl transferase‐mediated nick‐end labeling (TUNEL) assays. Metastasis of lungs was also evaluated by measuring number of metastatic nodules and wet weight of metastases. The proliferation of ECs and the tumor volumes in combination therapy group were inhibited more effectively than the other three groups at end point (P < 0.05). Cell clone assay showed anginex had radiosensitization effect on ECs. Immunohistochemistry showed tumors from mice treated with combination therapy exhibited the lowest MVD and proliferation rate, with highest apoptosis rate, as confirmed by IHC staining for CD34 and PCNA and TUNEL assays (P < 0.05). Combination therapy also induced the fewest metastatic nodules and lowest wet weights of the lungs (P < 0.05). rAAV‐anginex combined with radiotherapy induced apoptosis of osteosarcoma cells and inhibited tumor growth and pulmonary metastasis on the experimental osteosarcoma models. We conclude that the primary mechanism of this process may be due to sensitizing effect of anginex to radiotherapy.